POLITENESS STRATEGIES USED BY SENIOR HIGH SCHOOL STUDENTS IN LEARNING ENGLISH IN CENTRAL LAMPUNG - Novriyani (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2024)
Students interaction used politeness strategy helping learners develop the ability to communicate appropriately in different situations research was aimed to analyze the politeness strategies used by the students of senior high school. Politeness is an essential element of communication and is used to assure the quality of a relationship through language. Politeness in English classes is paramount to study because the sense of decency is indispensable. In another condition, virtual communication to some extent is challenging since it requires some rules to run proper interactions between lecturers and students. This involved descriptive qualitative research in which the research participants were forty participants. The data were spoken utterances of students performance. The data of politeness were analyzed based on (Brown & Levinson, 1987a). To achieve the purpose of study, the researcher used observation. The observation was done to observed and recorded of teaching and learning process. The research findings showed that Indonesian EFL learners tended to express annoyance when they made complaints. As for politeness, they mostly used bald on record and positive politeness. Social distance (D), rather than relative power (P), tended to influence the strategies of complaint and politeness